2020
DOI: 10.3390/sym12101638
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Job Scheduling Strategy Using Jobs Characteristics in Cloud Computing

Abstract: A crucial performance concern in distributed decentralized environments, like clouds, is how to guarantee that jobs complete their execution within the estimated completion times using the available resources’ bandwidth fairly and efficiently while considering the resource performance variations. Formerly, several models including reservation, migration, and replication heuristics have been implemented to solve this concern under a variety of scheduling techniques; however, they have some undetermined obstacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The proposed method minimizes the makespan however some more parameters need to be tested to find the performance of algorithm in multi-objective nature. Alsaih et al [6] developed a dynamic job scheduling model to map the jobs with resource based on available resources characteristics and also re-schedule the jobs that get allocated to VM. Proposed method minimizes the makespan, improved CPU utilization and bandwidth utilization.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method minimizes the makespan however some more parameters need to be tested to find the performance of algorithm in multi-objective nature. Alsaih et al [6] developed a dynamic job scheduling model to map the jobs with resource based on available resources characteristics and also re-schedule the jobs that get allocated to VM. Proposed method minimizes the makespan, improved CPU utilization and bandwidth utilization.…”
Section: Related Workmentioning
confidence: 99%
“…However, there are methods of resource provisioning like leased and reserved, which are used by big organizations [5]. The additional benefits of cloud computing are scalability, availability, reliability, flexibility, and sustainability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These values are used when the system load the machines. For the proposed WOA algorithm, the XML file also includes Pmin and Pmax values for each server because our algorithm is not only scheduling tasks but also calculating energy consumption by that particular machine during the task allocation as per Equation (4): Power Consumed = Pmin + (Pmax − Pmin) * Utilization where Pmin is set as minimum power consumed by the server in its ideal state and Pmax is the maximum power consumed by the server in its utilization state [ 55 ] and these values are set in the configuration file. These values have been set as 200 and 400 as min and max values, respectively, because it has found that most servers consume near to 200 Watts of power when they are in an ideal state and if they contain a large number of resources then they can consume nearly 400 Watts of power [ 56 , 57 , 58 ].…”
Section: Proposed Workmentioning
confidence: 99%
“…In such a scenario, the problem of resource assignments becomes more critical and challenging because it directly affects the performance of the Cloud system. Designing an efficient scheme for assigning resources to the workloads is known as scheduling strategy [11], face a lot of challenges. Scheduling is the process of decision making for mapping workloads (tasks) to Cloud computing resources to optimize some performance metrics like makespan, response time, resource utilization, and throughput [12]- [14].…”
Section: Introductionmentioning
confidence: 99%